The Effect of Workload and Work Motivation on the Performance of Nurses in the Arafah Inpatient Ward at Bogor Islamic Hospital - Agustin, Silvi; Hasudungan, Eddy Hermawan; Devi, Nurwulan Kusuma (International Journal of Business, Law, and Education, 2026)
This study aims to analyse the effect of workload and work motivation on nurses’ performance in the Arafah Inpatient Ward at Bogor Islamic Hospital. A quantitative, cross-sectional design was employed. The study utilised a saturated sampling technique, involving 35 nurses as respondents. Data were collected through questionnaires and analysed using multiple linear regression. The findings indicate that workload has a positive and statistically significant effect on nurses’ performance (t = 5.187; p < 0.001). Similarly, work motivation has a positive, statistically significant effect on nurses’ performance (t = 4.660; p < 0.001). Simultaneously, workload and work motivation significantly influence nurses’ performance (F = 77.219; p < 0.001), with an R² value of 0.828, indicating that 82.8% of the variance in nurses’ performance is explained by these two variables. It can therefore be concluded that both workload and work motivation exert a positive and significant influence on nurses’ performance in the Arafah Inpatient Ward at Bogor Islamic Hospital.